Gender Violence in the Film Posesif by Gina S. Noer and its Relevance as Indonesian Language Teaching Material - Tiara Anggun Safitri; Ali Imron Al-Ma’ruf (Borong Newinera Publisher, 2024)
Violence against women encompasses any kind of behavior that inflicts physical, sexual, or psychological damage against women. This study investigates the narrative structure of Gina S. Noer's film